Efeitos da press??o positiva nas vias a??reas, na responsividade br??nquica, na inflama????o, modula????o auton??mica e no controle cl??nico da asma de crian??as e adolescentes - David, Maisi Muniz Cabral (2016)
Context: Asthma is characterized by hyperreactivity of the airways. As for autonomic modulation, it is known that in asthmatic patients there is a predominance of parasympathetic activity, which is directly proportional to its severity, and an abnormal response of the autonomic nervous system (ANS) to exercise and the application of positive pressure in the Airways. From this contextualization two hypotheses emerged that were tested: positive airway pressure would act acutely in autonomic modulation post-exercise bronchoprovocation by exercise (BIE), outpatient treatment could reduce bronchial responsiveness. Objectives: To evaluate the autonomic modulation of HR, clinical responses during the bronchoprovocation test and during the application of positive pressure after the test (study 1); To evaluate the effects of positive pressure on bronchial hyperreactivity, pulmonary inflammation and clinical control of asthma (study 2). Methods: Two studies led to two studies, a cross-sectional study in which 55 patients with resting heart rate variability (HRV) were evaluated during the BIE (stable stretch) test, at rest after 10 'of BIE, and During positive pressure with pressure bile plus an anthropometric evaluation of inflammation and pulmonary function, and clinical control using the ACQ6 questionnaire. A blinded randomized controlled trial in which 64 patients were treated, 22 with CPAP = 12 and CPAP of 8, 22 with CPAP of 8 cmH2O and 20 as control group with respiratory muscle training (TMR), 40% inspiratory pressure Maximum. Patients were treated in the outpatient clinic for 10 sessions; the evaluations consisted of spirometry, bronchoprovocation test per exercise, manovacuometry, pulmonary inflammation (FeNO), clinical control (ACQ6). Both were approved by the ethics and research committee (opinion 1487225/2016) and the clinical trial was recorded in clinical trials (NCT-02939625). Results: Fifty-five asthmatic children were evaluated in the study 1, who were divided in response to bronchoprovocation test (GR) (n = 39) and no responder (GNR) (n = 16). A significant difference was observed in both the time domain (TD) and the HRV frequency domain, indicating inhibition of the parasympathetic nervous system during the BIE test, which did not return at baseline after 10 minutes of rest, but After the use of NIV in both groups, but the parasympathetic inhibition during the bronchoprovocation test in the GR was higher and more intense than in the GNR. In the study 2, 68 were evaluated and 64 children were treated. The 3 groups presented a clinical difference regarding the control of asthma, starting from a partial control for a total control (<0.75 with variation in the score> or = 0.5). In the bilevel group there was a reduction of FeNO of 17.4 ppb with effect size of 2.43 and reduction of bronchial responsiveness in the bronchoprovocation test, which before the treatment showed a reduction from the fifth to the twentieth minute and in the fifth to the tenth treatment only. In the CPAP group there was improvement in FeNO of 15.7 with effect size of 2.46 and reduction in bronchial responsiveness that before treatment showed a significant reduction of FEV1 from the fifth to the tenth and in the post only in the fifth. The TMR group showed no difference in lung function or responsiveness. Conclusion: Study 1 concluded that RG presented worse clinical control and a marked reduction in FEV1 at 5 and 10 minutes, in addition to a less stable autonomic regulation than GNR. In both groups, NIV assisted in the return of the autonomic activity to the basal levels after the bronchoprovocation test per exercise. Study 2, positive pressure therapy was shown to be effective in reducing bronchial responsiveness, pulmonary inflammation and clinical control of asthma.